2021
DOI: 10.3390/en14154690
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Artificial Intelligence Applications for Grid-Connected Solar Photovoltaic Systems

Abstract: The use of artificial intelligence (AI) is increasing in various sectors of photovoltaic (PV) systems, due to the increasing computational power, tools and data generation. The currently employed methods for various functions of the solar PV industry related to design, forecasting, control, and maintenance have been found to deliver relatively inaccurate results. Further, the use of AI to perform these tasks achieved a higher degree of accuracy and precision and is now a highly interesting topic. In this conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 197 publications
0
22
0
Order By: Relevance
“…Despite the holistic view proposed in this article, most of the published systematic literature reviews linked to solar PV have showed a technical focus, covering topics such as: advances in solar cell research and testing [18][19][20][21], energy losses and degradation of PV modules [22][23][24], forecasting of solar photovoltaic radiation and electricity generation [25,26], digital technologies for PV monitoring [27], and leaching of metals from EOL PV waste [28,29]. Other review articles have been more market-oriented, highlighting the need for government interventions in supporting PV diffusion [30]; the factors influencing residential households' adoption of PV systems [31,32]; and descriptions of the current PV market, its associated costs, and available technologies [33].…”
Section: Analytical Framework and Related Literaturementioning
confidence: 99%
“…Despite the holistic view proposed in this article, most of the published systematic literature reviews linked to solar PV have showed a technical focus, covering topics such as: advances in solar cell research and testing [18][19][20][21], energy losses and degradation of PV modules [22][23][24], forecasting of solar photovoltaic radiation and electricity generation [25,26], digital technologies for PV monitoring [27], and leaching of metals from EOL PV waste [28,29]. Other review articles have been more market-oriented, highlighting the need for government interventions in supporting PV diffusion [30]; the factors influencing residential households' adoption of PV systems [31,32]; and descriptions of the current PV market, its associated costs, and available technologies [33].…”
Section: Analytical Framework and Related Literaturementioning
confidence: 99%
“…Solar plant systems have complex nonlinear dynamics with uncertainties since the system’s parameters and insolation fluctuate [ 1 ]. Thereby, it is complicated to approximate these complex dynamics with classical methods, while ML methods provide the required performance [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thereby, it is complicated to approximate these complex dynamics with classical methods, while ML methods provide the required performance [ 2 ]. In modern sensor systems, ML methods are crucial units to increase the quality of big dataset processing for solar plant design, forecasting, maintenance, and control [ 1 , 2 ]. Within the EU COVID-19 strategic reply, the smart energy standards define a cloud platform specification for a distributed solar big data ecosystem that will provide the creation of effective ML technologies for smart solar energy [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most important variable in decision making for trading strategies is the photovoltaic power forecast. Reviews of photovoltaic power forecasting methods in [2], [3] conclude that Artificial Neural Networks (ANNs) are the most used artificial intelligence technique in solar power forecasting, as they have a proven track record in terms of accuracy for a variety of situations and with numerous input variables. Decision-makers of the energy sector need to understand how decision-aid tools construct their outputs from the data representing such dynamic multiscale systems.…”
Section: Introduction a Ai Applications In The Energy Sectormentioning
confidence: 99%